(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Honey, the unique, natural, liquid sweetening agent is produced by honey bees from the nectar of plants or from honeydew. Honey is also known to have many medicinal applications including antimicrobial, antibacterial, antifungal, anti-inflammatory and antioxidant activities. The composition of honey may vary due to geographical location, environmental and climatic conditions, plant species, as well as the methods employed during collection and storage of the honey. Honey contains different types of proteins, hormones, enzymes, vitamins, minerals, yeast, as well as organic acids, and principally sugars. This study was conducted in order to analyze and compare the mineral contents of the honey samples collected at the three senatorial districts of Kano state, with three honey samples collected from two local governments each from the three Senatorial Districts of Kano State, Nigeria. The mineral compositions of all the honey samples were determined using flame photometer and atomic absorption spectrophotometer. All the honey samples analyzed were found to be rich in K (247.49 to 251.73 µg/g); Na (137.16 to 147.53 µg/g); Ca (188.57 to 221.32 µg/g); Mg (76.49 to 78.83 µg/g) and Zn (31.15 to 48.92 µg/g), while Fe (6.84 to 14.27 µg/g); Mn (0.08 to 0.13 µg/g); Cu (0.12 to 0.25 µg/g); Ni (0.98 to 1.27 µg/g) and Pb (not detectable to 0.0002 µg/g) were found in smaller concentrations, The mineral compositions of all the honey samples were found to meet the international honey standards, and are therefore suitable for human consumption.